233k views
0 votes
B is incorrect so it's not the answer...

B is incorrect so it's not the answer...-example-1
User Ram G
by
5.1k points

1 Answer

3 votes

Answer:

x^2 - 4x - 3

Explanation:

f(x) = x^2 - 6x

g(x) = -2x + 3

(f - g)(x) is the subtraction of the functions, f(x) - g(x)

You need to write it carefully using parentheses for function g(x).

(f - g)(x) = f(x) - g(x) =

= x^2 - 6x - (-2x + 3)

Now take care of the parentheses by distributing the negative sign to its left. It will change every sign inside the parentheses.

= x^2 - 6x + 2x - 3

= x^2 - 4x - 3

User James Madison
by
5.4k points